Influence of wireless communication transport latencies and dropped packages on vehicle stability with an offsite steering controller. Issue 7 (14th May 2020) - Bennett, Rory; Kapp, Reyn; Botha, Theunis R.; Els, Schalk
Abstract : In recent years, advanced driver assistance systems (ADASs) have been used to improve the safety of vehicles by either providing additional information to the driver or by taking over complete control. The majority of ADASs currently being utilised run entirely on the vehicle, only having access to information provided by the sensors that are onboard the vehicle itself. Part of the next step in the evolution of ADAS is to incorporate information from other offsite sensors or obtain control inputs from infrastructure which can coordinate multiple vehicles simultaneously via a wireless interface. Wireless communication is inherently delayed and prone to dropped packets. This study looks at the effect of transport latencies and dropped packets on an off‐site autoregressive steering controller supplying direct steering inputs to a vehicle. A fully non‐linear vehicle simulation model is used to test the effect of delaying steering inputs and dropped packets to test the stability of the controller. The study shows that at dropped packet percentages of up to 40% adequate vehicle control is maintained, while transport latencies of up to 100 ms allow for moderately accurate vehicle control.